(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This comprehensive article explores the multifaceted landscape of simultaneous interpretation, emphasizing the pivotal role of speech compression in facilitating cross-linguistic communication. It delves into the nuanced strategies employed by interpreters to distill spoken language’s essence, condensing it into concise yet faithful renditions without compromising meaning. Drawing on linguistic principles and empirical studies, the article examines various compression techniques spanning syllabic, syntactic, lexical, and semantic dimensions. It investigates the theoretical underpinnings, practical implications, and adaptability of compression strategies across linguistic pairs and thematic domains. By offering novel insights into interpreters’ strategies, this article enriches our understanding of cross-linguistic communication dynamics, ensuring the seamless transference of meaning in real-time contexts.